Regional Variations in Sex Composition in Gandaki Province, Nepal (Research Journal of Padmakanya Multiple Campus, 2024)
Sex ratios are commonly used to predict or model population growth and are typically expressed as the number of males per 100 females. The sex composition of a population is a crucial characteristic in various demographic analyses. Separate data for males and females are vital not only for understanding the population structure but also for assessing the accuracy and completeness of population counts. Sex composition refers to the distribution of males and females within a population. Although the numbers of the two sexes are often not vastly different, their disparity has long been of interest to population geographers due to the contrasting roles of males and females in the economy and society of a region. This study is descriptive and based on secondary data, specifically from the 2021 census. The sex ratio data, readily available and accurately recorded during census enumeration, have been analyzed to assess changes in the sex ratio between 2011 and 2021. Gandaki Province, a leading and prominent region in Nepal in terms of population size, serves as the focus of this study. The findings of this research may be valuable for informing future development programs, particularly in terms of controlling population growth and understanding migration patterns.